Validation of physical properties of coals by conventional method with thermogravimetric analysis - Wan Zaiton, Wan Sulaiman; Mohd Fadzil, Mohd Idris; Jolius, Gimbun; Rafiziana, Md. Kasmani (AIP Publishing, 2025)
The validation of proximate analysis through drying the coals inside an oven or furnace (conventional) and thermogravimetric analysis (TGA) was done in this study. The purpose is to get an insight on the burning behavior during TGA analysis so that the method and the results can be used to replace the conventional method by drying in an oven. The chosen coals in this study were from two rank of coals; sub-bituminous coal, namely Tanito and bituminous coal namely Bayan. They were collected from a power plant located at Tanjung Bin, Johor. The properties of the coals were investigated through drying (oven) and burning (furnace) to get the value of volatile content, moisture content, and ash content according to British Standard procedures [1]. The same properties were also investigated through TGA according to ASTM International method [2]. The results have shown a good reproducibility with an error of 1.62% for volatility, 0.95% for moisture content, and 0.24% for ash content. The results can be utilized to classify the rank of coal, to get the proportion of combustible and incombustible components and also for various purposes in industry. Besides that, analysis through TGA is able to give faster results as compared to conventional method.